KEPEMIMPINAN BERBASIS OUTPUT PADA PAUD - Ardina Risdiyana; Laili Sofwaturrohmah; Maulia Dwi Apriani; Siswadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Leadership in Early Childhood Education (ECE) plays a strategic role in determining the quality of children’s educational outcomes. However, leadership practices that remain focused on administrative aspects and learning processes pose challenges in achieving optimal educational outputs. This study aims to analyze the concept of output-based leadership in ECE, identify its underlying principles, and examine the strategies and challenges in its implementation. The method used is qualitative research with a literature study approach, drawing on national and international journal sources from the last five years. Data collection was conducted through documentation studies, while data analysis employed the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results indicate that output-based leadership emphasizes the achievement of holistic child development, encompassing cognitive, socio-emotional, and character aspects. The main supporting principles include service, persuasion, guidance, efficiency, and sustainability. Effective implementation strategies involve transformational, instructional, and collaborative leadership. The challenges faced include limited leadership competencies, insufficient resources, constraints in implementing holistic-integrative programs, and low involvement of parents and the community. Therefore, strengthening leadership capacity and fostering collaboration among stakeholders are essential to sustainably improve the quality of ECE outcomes.